Asparagine Synthetase Expression and Phase I Study With L-Asparaginase Encapsulated in Red Blood Cells in Patients With Pancreatic Adenocarcinoma. Issue 7 (October 2015) - Bachet, Jean-Baptiste; Gay, Fabien; Maréchal, Raphaël; Galais, Marie-Pierre; Adenis, Antoine; MsC, David Salako; Cros, Jerome; Demetter, Pieter; Svrcek, Magali; Bardier-Dupas, Armelle; Emile, Jean-François; Hammel, Pascal; et al.
Abstract : Objectives: Asparaginase encapsulated in erythrocytes (ERY-ASP) is a potentially effective drug in patients with pancreatic adenocarcinoma (PAC) with null/low asparagine synthetase (ASNS) expression. Our aims were to assess ASNS expression in PAC from a large cohort and its prognostic and/or predictive value and to conduct a phase I trial with ERY-ASP in patients with metastatic PAC. Methods: Asparagine synthetase expression was evaluated using immunohistochemistry in resected PAC (471 patients) and in pairs of primary tumor and metastases (55 patients). Twelve patients were included in the phase I trial and received a single administration of ERY-ASP (25-150 IU/kg). Results: Null/low ASNS expression was found in 79.4% of the resected PAC with a high concordance between primary tumor and metastases. Asparagine synthetase expression was significantly correlated with sex and CXCR4 expression. In the phase I trial, ERY-ASP was well tolerated by patients with metastatic PAC. No patient had DLTs, and 6 patients had at least 1 ERY-ASP causally related adverse event out of the 12 adverse events reported. Conclusions: Given the high rate of PAC with null/low ASNS expression and the good tolerability profile of ERY-ASP, ERY-ASP should be evaluated in further clinical studies in metastatic PAC. Abstract : Supplemental digital content is available in the text.